(untitled) (Journal of the College of Basic Education, 2022)
The research included the preparation of a polymeric nanocomposite consisting of mixing epoxy and urethane rubber at a ratio of (15) to which nano-alumina particles were added with a weight ratio of (0,2.5,5,7.5,10) and compared with the same mixture to which nano titania particles were added with the same weight ratios as before. The remembrance.